(untitled) (ABDIMAS: Jurnal Pengabdian Masyarakat, 2022)
Along with the declining number of Covid-19 cases, in January 2021 the government has suggested classroom teaching for green zones. Activities at school will return to running as usual, namely by holding face-to-face learning. According to the head of the Hidayatullah Islamic Boarding School in Cilengkrang, so far there have been no cases of COVID-19 and all students are in good health. However, it was found that Islamic boarding schools do not yet have a clear flow related to health protocols, especially in dealing with classroom teaching, there are still many students who have not been vaccinated because they are worried about being vaccinated, and compliance with health protocols is starting to decrease because they think that Covid-19 cases are starting to decline and are still declining, lack of knowledge of students to improve the immune system one of them with herbal plants. The solutions given in overcoming the partner’s problems are conducting counseling about students’ readiness for classroom teaching, counseling about Covid-19 vaccination, counseling about tips to improve the immune system, and demonstrations on the use of herbal plants to improve the immune system. The method of implementing this community service activity is directly/offline which is carried out in Islamic boarding schools, the targets are students, teachers, and school employees who are invited to take part in community service activities. The result of this activity is the implementation of a series of counseling activities, simulations, and demonstrations attended by students, teachers, and school staff as planned. All participants in each activity can follow to the end with a conducive and enthusiastic.